Leitura literária temática no ensino médio: princípios e orientações metodológicas - Lourenço, Suéllen Pereira Miotto (2021)
Starting from a data exposition that situates reading as a challenging issue for the Brazilian education, we place our dissertation within the scope of literary reading in school environment, particularly problematizing the issue of teaching literary reading in the high school context. Many researchers in the field (AGUIAR; BORDINI, 1988; ZILBERMAN, 1986; LEAHY-DIOS, 2000; CEREJA, 2004; DALVI, 2013b, 2014) have recognized for some time that the teaching of literature is limited to the use of texts – or fragments – to exemplify “literary schools” in lectures have not collaborated with the objectives of teaching Literature, nor have generated effective social practices of literary reading. In this scenario, we intend to offer methodological principles and guidelines that aim to the full reading of literary texts with high school students and the development of pedagogical practices that consider the literary text not as a "product of the environment" (direct consequence of a given social context, articulated to a given "literary school"), but as a human creation that has a complex origin and purpose and that extrapolates the schematism given by the direct link between historical context, period or literary school and exemplary text (“representative” of characteristics attributed to the period or literary school). We aim, through the mediation of a thematic literary reading, to provide opportunities for the appropriation of the most sophisticated set of knowledge historically produced by humanity and essential for the full development of the individual. We established, therefore, as the general objective of this dissertation, through a theoretical-bibliographic research, to systematize principles and guidelines for pedagogical work in school context, which unfold into a proposal for thematic reading of literary texts at high school level. For this, we based ourselves in the conceptual notions of dialogism, theme, and responsiveness, drawn from the Bakhtin Circle; in reflections on the relationship between literature and reading by Antonio Candido; in Lev Vygotski's conception of mediation; and in the historical-critical pedagogical theory, as collective development. We selected the theme Family Relations to be the motto for the analysis of four texts (“História de Passarinho”, by Lygia Fagundes Telles; “Passeio Noturno”, by Rubem Fonseca; Boitempo, by Carlos Drummond de Andrade; Minha Vida de Menina, by Helena Morley) in order to favor an understanding of the symbolic, formal and historical aspects present in literary language. With this work, we seek to contribute to the promotion of a dialogical and meaningful literary reading, based on the premise that educational practice must always aim at the omnilateral human formation of a subject who will socially interact and constitute the collectivity, transforming reality.